THE ACCUMULATING EFFECT OF FOOT MASSAGE IN RELIEVING ACUTE POSTOPERATIVE PAIN IN INDONESIAN PATIENTS AFTER ABDOMINAL SURGERY - Chanif -; Mustofa - A (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Foot massage is a non-pharmacological nursing intervention that can be used as acomplementary therapy in relieving acute postoperative pain in patients after abdominal surgery.This study aimed to examine the accumulating effects of foot massage in relieving acutepostoperative pain. Twenty patients after abdominal surgery were selected as subjects. Five hours and sevenhours after patients had received Ketorolac 30 mg injection IV, the 30-minute foot massage wasapplied to the experimental group for two sessions on the first day (24-48 hours) afterabdominal surgery. A Visual Numeric Rating Scale (VNRS) was used to measure the pain score. Pain intensity and pain distress were measured across four time measures: at T1 (beforegiving the first session of foot massage), T2 (30 minutes after T1), T3 (120 minutes after T1 orbefore giving the second session of foot massage), and T4 (150 minutes after T1 or 30 minutesafter T2). Data were analyzed using non parametric tests including the Wilcoxon match pairedrank test and Friedman’s test. The findings revealed that both the pain intensity scores and the pain distress scores inafter receiving foot massage (T2 and T4) were lower than those of before receiving the footmassage (T1 and T3) (p<.001). The scores stepped down and the lowest scores were at T4.These findings confirm that foot massage did work in reducing pain intensity and pain distressacross times.Keywords: foot massage, pain intensity, pain distress, abdominal surgery.